جمع القرآن بعہد صدیقی ؓ کے مرکزی راوی عبید بن سبّاق پر علامہ تمنا عمادی کا نقدایک تحقیقی وتنقیدی مطالعہ: A Theological Review of the Opinion of Allama Tamana Emadi on Obaid bin Sabaaq Regarding the Compilation of Quran - Saeed Ahmad,; Dr. Abdul Hameed Khan Abbasi, (MEI, 2023)
The summary of this research paper is that the theory of majority of Muslim Ummah’s Scholars regarding the Holy Qur'ān’s compilation is that although it was in written form in the era of Prophet Muhammad (PBH) in different writing instruments, but the trust was on memorization in heart which was Arab's specialty. so when the Messenger of Allah (PBUH) died , the Holy Qur'ān was preserved in the hearts of thousands of companions, as well as the various instruments which were also written in divided booklets, but the Qur'ān was not present in the form of a book as its today.Later on it was collected by Zaid bin Thābit in the era of Abū Bakr Siddique on the advice of 'Umar and once again in the era of 'Uthmān Ghani when the extremist approach seen in society due to “IKHTLAF-E- QIRA’T” in some areas of Islamic state. He formed a committee in the leadership of Zaid ibne Thābit which set the various prescriptions of the Qur'ān from the Prescription of Abū Bakr and sent to the different parts of the State. But the approach of Allāma Tamannā 'Emādi is completely different because in his opinion the Qur'ān was present in the form of one book in the days of Muhammad (PBUH) because he was ordered by Allah to preach the message it is not possible that he left the world while the Holy Qur'ān was not in complete, book, then there are various verses of the Holy Qur'ān which clearly mention that it was in written shape that time. According to his approach all the Narrations regarding compilation of the Holy Qur'ān in the era of Abū Bakr and then, 'Usmān are fake and made by non-Arabs.The purpose of which was to suspend the position of the Qur'ān, And the false narrators like 'Ubaid bin Sabbāq participated in this conspiracy. In this research article, the criticism of 'Allāma Tamannā's approach on 'Ubaid bin Sabbāq has been reviewed and realistic efforts have been made to inform readers according to the laws of جرح وتعدیل in Islām.